Labour Rights Protection in Industrial Relations Issues - Eko Adi Susanto (Rechtsidee, 2015)
Many violations of the terms of employment at Surabaya, employment protection and working conditions for workers who are not provided by employers to the maximum, according to the legislation in force, while the legal protection for workers constrained because of the weakness in the system of employment law, both the substance and the culture built by governments and companies. How To Cite: Susanto, E. (2015). Labour Rights Protection in Industrial Relations Issues. Rechtsidee, 2(2), 109-120. doi:http://dx.doi.org/10.21070/jihr.v2i2.78